School’s Strategy for Teacher’s Professionalism through Digital Literacy in the Industrial Revolution 4.0 - Desi Agustini; Bukman Lian; Artanti Puspita Sari (INTERNATIONAL JOURNAL OF EDUCATIONAL REVIEW, 2020)
This research aimed at describing school's strategy in increasing the professionalism of Primary School teachers through Digital Literacy. This research was conducted at SD Negeri 6 Pulau Rimau, Banyuasin. The method was descriptive qualitative. Data collection techniques using interviews, observation, and documentation. The results of the study approved the Principal's strategy and the role of the teacher to improve teacher’s professionalism through digital literacy run effectively. Some of the strategies used by principals include completing facilities and targets that can support digital literacy, strengthening literacy through e-Learning, school strategies by sending teachers and education personnel to get seminars, training, or technical assistance and helping Teacher Working Groups or Groups Principal's Work. Teacher strategies in increasing professionalism by implementing four teacher competencies, pedagogical, personal, social, and profesional competence through digital literacy.